Comments on ''Evaluation of Knowledge and Attitudes of Dentists and Dental Students about Oral Cancer - Manas Bajpai (Current Research in Dental Sciences, 2025)
To the editor,I read the article titled ‘Evaluation of Knowledge and Attitudes of Dentists and Dental Students about Oral Cancer by Altındal D 1. I found this article enlightening and interesting. I am practicing Oral Pathology in India from last 13 years, the attitude and knowledge of the dentists and dental students is similar in India. As frontline healthcare providers, dentists and dental students play a pivotal role in identifying suspicious lesions and initiating appropriate referrals. However, despite advancements in diagnostic technologies and treatment modalities, a gap often exists in the knowledge and confidence of dental professionals to effectively manage oral cancer concerns. Traditional lectures and textbooks are no longer sufficient to keep pace with the rapidly evolving landscape of oral cancer research. 2 Modern educational approaches embrace technology to deliver engaging and accessible learning experience.3 Interactive online modules can incorporate real life case studies, high resolution images of oral lesions and interactive quizzes to reinforce learning. Virtual reality can simulate clinical scenarios, allowing students to practice oral cancer examination and biopsies in a safe and controlled environment. Connecting students and junior dentists with experienced oral pathologists, oral surgeons and oncologists through tele-mentoring platforms facilitates knowledge transfer and provides real-time guidance on complex cases